Integrating Blambangan Culture of Banyuwangi into Elementary Science Education: An Ethnoscience Approach - Wardani, Rizki Putri; Nuriman; Zahro, Khoirunnisa Az; Alfaroidz, Ahmad Saddam Hussein (International Journal of Elementary Education, 2024)
The integration of local culture into science learning poses a significant challenge in enhancing the relevance of instructional materials to daily life. This study aims to analyze the Blambangan Culture of Banyuwangi through an ethnoscience approach in elementary science education. A qualitative research method was employed, using data collection techniques such as observations and interviews with cultural experts. Data analysis was conducted using the theory by Miles, Huberman, and Saldana, involving stages of data collection, data presentation, data reduction, and conclusion drawing. The findings reveal the mapping of elementary science materials with the Blambangan Culture of Banyuwangi through an ethnoscience approach. The cultural elements analyzed include mepe kasur, gintangan, gedhogan, metik padi, petik laut, and batik gajah uling. Relevant science topics include force and energy, plants, sound and waves, as well as terrestrial and marine ecosystems. This study concludes that the mapping results can serve as the foundation for developing more contextual teaching materials through an ethnoscience approach, thereby improving students' understanding of science concepts grounded in local culture.